Can acetate replace bicarbonate in oral rehydration solution for infantile diarrhoea?. Issue 8 (August 1982) - Patra, F C; Mahalanabis, D; Jalan, K N; Sen, A; Banerjee, P
Abstract : In a double-blind trial two groups of 20 infants and young children suffering from diarrhoeal dehydration and acidosis were successfully treated with an acetate and a bicarbonate containing oral rehydration solution. The former was found to be as effective as the latter and was equally acceptable to the patient.